C iv black hole mass measurements with the Australian Dark Energy Survey (OzDES). Issue 3 (5th June 2019) - Hoormann, J K; Martini, P; Davis, T M; King, A; Lidman, C; Mudd, D; Sharp, R; Sommer, N E; Tucker, B E; Yu, Z; Allam, S; Asorey, J; et al.
ABSTRACT: Black hole mass measurements outside the local Universe are critically important to derive the growth of supermassive black holes over cosmic time, and to study the interplay between black hole growth and galaxy evolution. In this paper, we present two measurements of supermassive black hole masses from reverberation mapping (RM) of the broad C iv emission line. These measurements are based on multiyear photometry and spectroscopy from the Dark Energy Survey Supernova Program (DES-SN) and the Australian Dark Energy Survey (OzDES), which together constitute the OzDES RM Program. The observed reverberation lag between the DES continuum photometry and the OzDES emission line fluxes is measured to be $358^{+126}_{-123}$ and $343^{+58}_{-84}$ d for two quasars at redshifts of 1.905 and 2.593, respectively. The corresponding masses of the two supermassive black holes are 4.4 × 10 9 and 3.3 × 10 9 M⊙, which are among the highest redshift and highest mass black holes measured to date with RM studies. We use these new measurements to better determine the C iv radius−luminosity relationship for high-luminosity quasars, which is fundamental to many quasar black hole mass estimates and demographic studies.